Eficiência do geotextil no processo de filtração da água na Ufersa, campus Pau dos Ferros - Moura, Thallysmara Roberta Freitas de (Universidade Federal Rural do Semi-Árido, 2019)
With the development that the world has been suffering in the last decades, the population growth has accelerated, which requires new techniques to meet the needs of society. Access to drinking water is a matter of concern, and with this new sources and treatment techniques to meet potability are necessary, since, for some countries, their access meets the needs of their populations, while other countries such resource is available only for a portion, and yet, in limited condition, in quantitative and / or qualitative terms. The Northeastern semiarid region is one of the areas hardest hit by water scarcity, due to its semiarid climatic conditions, associated to the degradation of water resources, caused mainly by anthropic action. Thus, it is necessary to think of technologies for the treatment of water, in materials such as geosynthetics that function as a filter in a similar way to conventional granular filters and can also be used as a filter element aiming at the reduction of pollutant potential leachates and residues, thus being a material to be studied for water filtration processes. In this scenario, the objective was to analyze the efficiency of the non-woven geotextile in the water filtration process that supplies UFERSA - Campus Pau dos Ferros. A sample collection was carried out, to which 78 experiments were carried out, at different supply points in the blocks of the UFERSA Irons' Campus, as well as physical-chemical characterization of the water supply before and after the filtration process with the implementation of the synthetic geotextile filter. In the characterization of the samples, the blanket was effective in increasing the pH, in the reduction of dissolved solids, in the increase of dissolved oxygen, in the reduction of temperature, in the turbidity, and also in other parameters. Regarding turbidity, in some experiments, the geotextile presented improvements in the parameter, but in others it increased significantly, which could possibly have been caused due to the presence of impurities in the blanket presenting the need for a treatment of this material, being able to show itself more efficient in processes. It is possible to observe through the analyzed parameters the influence that certain parameters have on the others, which influences the quality of the water.
Keywords: Tratamento da água; Caracterização físico-química; Qualidade da água; Water treatment; Physical-chemical characterization; Water quality; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA